2019
DOI: 10.1007/s13197-018-03556-x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and antimicrobial susceptibility of Staphylococcus aureus isolated from ready-to-eat foods of animal origin from tourist destinations of North-western Himalayas, Himachal Pradesh, India

Abstract: This study was aimed to determine the incidence of Staphylococcus aureus in ready-to-eat (RTE) milk (n = 120) and meat (n = 120) products from various tourist places in north western Himalayas, Himachal Pradesh, India. S. aureus isolates and its enterotoxins; A, B, D and E were characterized by conventional and molecular methods. Antimicrobial susceptibility (AMS) profiles of S. aureus isolates were determined by disk diffusion method using Clinical and Laboratory Standards Institute criteria. Overall, 6.7% (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Because our samples were from 25 provinces across China, our research is more representative of the entire country than the studies that focused on individual provinces. Similarly, we demonstrated a lower MDR prevalence (26.1%) than previous reports from Shaanxi, China (58.6%) [37] and Himachal Pradesh, India (81.3%) [3]. The greatest resistance was to PCN (87.3%), which is in agreement with the findings iin Sichuan province (90.7%) [18] and our previous study (83.7%) [33].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Because our samples were from 25 provinces across China, our research is more representative of the entire country than the studies that focused on individual provinces. Similarly, we demonstrated a lower MDR prevalence (26.1%) than previous reports from Shaanxi, China (58.6%) [37] and Himachal Pradesh, India (81.3%) [3]. The greatest resistance was to PCN (87.3%), which is in agreement with the findings iin Sichuan province (90.7%) [18] and our previous study (83.7%) [33].…”
Section: Discussionsupporting
confidence: 92%
“…infections, implanted medical device-related infections [3,4], and bacteremia, which is associated with a high mortality rate [5].…”
mentioning
confidence: 99%
“…For the first time, Bakshi [60, 61] described the morpho‐anatomical features of ectomycorrhizae of C. deodara . Thereafter several studies have observed EcM association with this tree species [21, 61–73]. Moreover, many researchers have successfully synthesized Rhizopogon ectomycorrhizae with several conifer species under laboratory conditions [25, 74–83], beside this, the seedlings of C. deodara have been inoculated with pure cultures of several EcM fungi other than Rhizopogon sp [84–87].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it was previously been found by other workers in 23% of ice-creams in northern Turkey [22 ; ] 40% of yogurts, 28% of butter, and 74% of ice-creams in Egypt [39 ; ] 5.3% of butter (in which S. aureus counts were above 10 5 CFU/g), 5.6% of creams, and 5.9% of traditional ice-creams in Iran [40 ; ] 38% of ice-creams in Libya [41 ; ] 10.0% of ice-creams in northern India. [42] High numbers of S. aureus (~1.4 x 10 6 CFU/Ml) were isolated from ice-creams in Rio de Janeiro, Brazil. [43] The high percentages of S. aureus in those studies could have been the resulted from the contamination of raw milk at the farm level from the milk-producing animal and the environment, utensils used for milking, or from dairy workers during the artisanal processing at different stages.…”
Section: Presence Of S Aureus In Raw Milk and Traditional Artisanal Dairy Foodsmentioning
confidence: 99%